Proteolytically active ADAM10 and ADAM17 carried on membrane microvesicles in human abdominal aortic aneurysms - Folkesson, Maggie; Li, Chunjun; Frebelius, Siw; Swedenborg, Jesper; Wågsäter, Dick; Williams, Kevin Jon; Eriksson, Per; Roy, Joy; Liu, Ming-Lin (Thrombosis and Haemostasis, 2015)
The intraluminal thrombus (ILT) of human abdominal aortic aneurysm (AAA) has been suggested to damage the underlying aortic wall, but previous work found scant activity of soluble proteases in the abluminal layer of the ILT, adjacent to the aneurysm. We hypothesised that transmembrane proteases carried by membrane microvesicles (MV) from dying cells remain active in the abluminal ILT. ILTs and AAA segments collected from 21 patients during surgical repair were assayed for two major transmembrane proteases, ADAM10 (a disintegrin and metalloprotease-10) and ADAM17. We also exposed cultured cells to tobacco smoke and assessed ADAM10 and ADAM17 expression and release on MVs. Immunohistochemistry showed abundant ADAM10 and ADAM17 protein in the ILT and underlying aneurysmal aorta. Domain-specific antibodies indicated both transmembrane and shed ADAM17. Importantly, ADAM10 and ADAM 17 in the abluminal ILT were enzymatically active. Electron microscopy of abluminal ILT and aortic wall showed MVs with ADAM10 and ADAM17. By flow cytometry, ADAM-positive microvesicles from abluminal ILT carried the neutrophil marker CD66, but not the platelet marker CD61. Cultured HL60 neutrophils exposed to tobacco smoke extract showed increased ADAM10 and ADAM17 content, cleavage of these molecules into active forms, and release of MVs carrying mature ADAM10 and detectable ADAM17. In conclusion, our results implicate persistent, enzymatically active ADAMs on MVs in the abluminal ILT, adjacent to the aneurysmal wall. The production of ADAM10- and ADAM17-positive MVs from smoke-exposed neutrophils provides a novel molecular mechanism for the vastly accelerated risk of AAA in smokers.Portions of this work were presented at the Arteriosclerosis, Thrombosis and Vascular Biology 2012 Scientific Sessions, 19 Apr 2012 (ref. 25), and in a doctoral thesis defense February 2013 (ref. 26).
Keywords: Abdominal aortic aneurysm; ADAM10; ADAM17; intraluminal thrombus; A disintegrin and matrix metalloproteinase; membrane-bound protease; microparticles; microvesicles